2011
DOI: 10.1007/s10854-011-0522-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of annealing time and temperature on structural and superconducting properties of (Bi, Pb)-2223 thin films produced by sputtering

Abstract: This study reports the effect of annealing time (15 min, 1.5 and 3 h) and temperature (850, 860 and 870°C) on the structural and superconducting properties of thin films by means of scanning electron microscopy (SEM), X-Ray analysis (XRD), electron dispersive X-Ray (EDX), resistivity and transport critical current density (J c ) measurements. Zero resistivity transition temperatures (T c ) of the films produced are estimated from the dc resistivity measurements. In addition, the phase and lattice parameters ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…In a recent study [38], the role of annealing time and temperature on structural and superconducting properties of (Bi, Pb)-2223 thin films produced by sputtering was investigated and it was found the greatest Bi-2223 phase fraction belongs to the film annealed at 860°C for 3 h. In the present work, we state the effect of the various annealing temperature and time on the microstructure and transport properties of the thin films produced by magnetron reactive sputtering method by means of X-Ray analysis (XRD), scanning electron microscopy (SEM), electron dispersive X-Ray (EDX), resistivity and critical current density (J c ) measurements. The results show that the superconducting thin film annealed at 840°C for 6 h obtains the highest T offset c and J c value among the films prepared.…”
Section: Introductionmentioning
confidence: 93%
“…In a recent study [38], the role of annealing time and temperature on structural and superconducting properties of (Bi, Pb)-2223 thin films produced by sputtering was investigated and it was found the greatest Bi-2223 phase fraction belongs to the film annealed at 860°C for 3 h. In the present work, we state the effect of the various annealing temperature and time on the microstructure and transport properties of the thin films produced by magnetron reactive sputtering method by means of X-Ray analysis (XRD), scanning electron microscopy (SEM), electron dispersive X-Ray (EDX), resistivity and critical current density (J c ) measurements. The results show that the superconducting thin film annealed at 840°C for 6 h obtains the highest T offset c and J c value among the films prepared.…”
Section: Introductionmentioning
confidence: 93%
“…According to the broadening nature of the XRD peaks of the ceramic, the particle size can be determined from the Scherrer-Warren equation [31][32][33][34].…”
Section: Grain Size Calculationmentioning
confidence: 99%
“…In addition, the Bi-2223 lead with a high phase-forming temperature and a low melting point is often added to form some liquid phases so as to lower the reaction temperature and promote the reaction [26][27][28]. Yildirim et al fabricated a (Bi, Pb)-2223 thin film through sputtering and found that the (Bi, Pb)-2223 phase content in the film obtained after 3 h of annealing at 870 • C was up to 88.65% [29]. Qu et al produced a (Bi, Pb)-2223 thin film with a thickness of about 100 nm on a LAO single-crystal substrate.…”
Section: Introductionmentioning
confidence: 99%